Teacher education research in the UK: the state of the art - Menter, Ian; Hulme, Moira; Murray, Jean; Campbell, Anne; Hextall, Ian; Jones, Marion; Mahony, Pat; Procter, Richard; Wall, Karl (Swiss Journal of Educational Research, 2010)
This paper offers an analysis of the current state of teacher education research in the United Kingdom (UK). It commences with a brief historical overview of developments over the last century. Some recent «capacity building» initiatives designed to enhance and develop teacher education research are described. There is then a focus on a particular web-based resource that draws together a significant number of publications in UK teacher education research from 2000-2008. This database is then analysed in order to identify in which journals and by which authors this work is produced. The range of methodological approaches and substantive areas of focus that appear to predominate in teacher education research in the UK are reviewed, according to categories within the database. This demonstrates that there are some very real challenges to be faced by teacher education researchers in the years ahead, similar but not identical to those faced elsewhere.